Reconcentrating the Ionic Liquid EMIM-HSO4 Using Direct Contact Membrane Distillation - Mark J. Wong; Viral Sagar; Joan G. Lynam (Molecules)
Adequate water supplies are crucial for missions to the Moon, since water is essential for astronauts’ health. Ionic liquids (ILs) have been investigated for processing metal oxides, the main components of lunar regolith, to separate oxygen and metals. The IL must be diluted in the process. Recycling this diluted IL post-processing is important to reduce the materials required in resupply missions. In addition, water will be needed in lunar greenhouses for growing food and aiding in sustaining a habitable environment. Direct contact membrane distillation (DCMD) is a new technology for water purification that was examined in this study for its feasibility to concentrate IL. Hydrophobic membranes composed of polytetrafluoroethylene (PTFE) and polyvinylidene (PVDF) were found to hold promise in separating solutes from water to concentrate a diluted IL solution and to recover water. A bench-scale DCMD system was employed to test this method at temperatures of 50 °C, 65 °C, and 80 °C. Hence, the benefits and limitations of DCMD with PTFE and PVDF membranes were explored for the aqueous IL 1-ethyl-3 methylimidazolium hydrogen sulfate for DCMD performed at different temperatures.